Bacteria associated with respiratory tract infections in rabbits - Jini Jeorge (Department of Veterinary Microbiology, College of Veterinary and Animal Sciences, 2009)
A study was undertaken to isolate the bacteria associated with respiratory tract infections in rabbits. In this study, isolation, identification and antibiotic susceptibility of the isolates as well as determination of their pathogenicity to mice were carried out. Samples were collected from ailing and dead rabbits. Nasal swabs from the ailing rabbits showing clinical signs such as nasal discharge and respiratory distress, tracheal and lung samples of the dead rabbits with post mortem lesions such as pneumonia, congestion of lungs and haemorrhages of trachea were collected for the isolation trials. These samples were collected from rabbit farm attached to Kerala Agricultural University, commercial farms in Malapuram district, dead rabbits brought to Centre of Excellence in Pathology for post mortem and ailing animals brought for microbiological examination to the Department of Veterinary Microbiology. A total of 62 samples were collected, comprising of 30 nasal swabs, 25 lung samples and 7 tracheal swabs, for the isolation of the organisms.